Теоретические истоки и особенности институционализации социологии окружающей среды - Стегний, А. (Iнститут соціології НАН України, 2009)
In the article, the theoretical origins of environmental sociology in a classic sociological theory are examined. The basic stages of genesis of eco-sociological theory are analyzed in detail, particularly such directions in sociology, as social Darwinism, geographical school, as well as K. Marx's, E.Durkheim's, and M.Weber's views on the interrelations between society and its natural environment. Special attention is paid to socio-ecological conception of Chicago school of Urban sociology, Human ecology, Duncan-Schnore's Ecological complex theory. The disparateness of conceptual content of notions of social ecology and sociology of natural environment is also as certained in the article. Whereas a social context and theoretical origins of environmental sociology in the West and in the former USSR appreciably differ, the features of institutionalization of Western and (Post-) Soviet Environmental Sociology are examined at length.